THE IMPACT OF POLICE BUREAUCRATIC REFORM ON IMPROVING THE QUALITY OF HUMAN RESOURCES (STUDY IN BATTALION A PIONEER OF THE DIY REGIONAL POLICE BRIMOB SAT) - Tri Jaka; Sugiyanto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Bureaucratic reform within the Indonesian National Police (Polri) is a strategic step in building professional, transparent, and public service-oriented organizational governance. This study aims to analyze the dynamics of bureaucratic reform of Polri human resources (HR) through three main phases, namely Trust Building (2004–2009), Partnership Building (2010–2014), and Strive for Excellence (2015–2025), with a focus on the study of Battalion A Pelopor Mobile Brigade Unit (Satbrimob) Polda Istimewa Yogyakarta. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation studies. The results show that in the Trust Building phase (2004–2009), bureaucratic reform focused on internal organizational improvements through increasing discipline, professionalism, and establishing a work culture with integrity to rebuild public trust. In the Partnership Building phase (2010–2014), Polri strengthened institutional synergy and strategic partnerships with the community and government institutions to improve the effectiveness of task implementation. Meanwhile, in the Strive for Excellence phase (2015–2025), reforms are directed at improving the quality of competency-based human resources, digitizing performance management systems, and strengthening organizational governance toward a superior, adaptive, and sustainable institution. This research confirms that the success of Polri's human resource bureaucratic reform is largely determined by continuity between phases and institutional commitment to upholding professionalism, integrity, and a work culture that is responsive to change.